Niveles de resistencia de genotipos promisorios de Cacao (Theobroma cacao L.), colección ICT para moniliophthora roreri en la región San Martín. - Sánchez Torres, Gina Paola (2011)
In Peru, very few studies have focused on the selection of genotypes with resistance to frosty pod and other diseases, however, in recent years did work cocoa collection basin of the Ucayali and Huallaga, to select promising genotypes of cacao collection ICT with higher levels of resistance to M. roreri. The genotypes were evaluated by artificial infection under natural infection conditions in the U.S.-The Choclino, managed under the traditional system (TS). Artificial inoculation inoculum for the pathogen in fruits of three months of age obtained by controlled pollination, eight weeks after inoculation were evaluated external severity (ES) and internal (SI) of the fruit. genotypes and ICT- 2161 y ICT- 2504 were classified as susceptible (ISI> 3,76), ICT-1281; ICT-2702; ICT-2174; ICT-2705; ICT-2173; ICT-1026 and ICT-1382 moderately susceptible (3,75 > ISI> 2,51) and ICT-2171; ICT-2315; ICT-1104; ICT-2492; ICT-1189; CT-1414; ICT-2501; ICT-2175; ICT-2165; ICT-2825; ICT-2703 and ICT-2152 moderately resistant (2,51> ISI> 1,25). genotypes while ICT-2821; ICT-1043; ICT-1561; ICT-1087; ICT-1251; ICT-1506; ICT-1187; ICT-1292; ICT-1182; ICT-1092; ICT-2824; ICT-1176; ICT-2653; ICT-2142; ICT-2172; ICT-1112; ICT-2823 and ICT-2163 were classified as resistant (1,25> ISI> 0,0). For Natural infection was moniliasis assessments every 30 days. We calculated the incidence and AUDPC. genotypes ICT- 1026; ICT- 1043; ICT- 1187; ICT- 1251; ICT- 1292; ICT- 1382; ICT- 1414; ICT- 2161; ICT- 2165; ICT- 2174; ICT- 2315; ICT- 2504; ICT- 2821 and ICT-2825 with AUDPC <50, showed resistance to M. roreri. While genotypes, ICT-1043, ICT-1187, ICT- 1251, ICT- 1292, ICT- 2821 were classified as resistant to infection with M. roreri both artificial and natural inoculum.